2020
DOI: 10.1080/16878507.2019.1695382
|View full text |Cite
|
Sign up to set email alerts
|

Medical exposure and risk estimation during routine radio-diagnostic examinations in Agadir City in 2012

Abstract: We evaluated medical exposure and risk estimation during routine radio-diagnostic examinations in Agadir City during the year 2012. The frequency data were collected from four main Radiological departments of the city performing radiography as well as computed tomography (CT) procedures. The estimated annual number of examinations was approximately 100.000. Eighty percent of diagnostic examinations were conventional radiology procedures while CT exams represent only 20%. The evaluated annual number of examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Despite the growing number of CT machines in Morocco, the Diagnostic Reference Levels (DRL) have yet to be defined. Thus, several previous studies have shown a significant variation in the doses administered to patients for the same radiological examination procedure [ 20 - 26 ]. The aim of this pilot study at Hassan II Hospital of Agadir was to estimate the doses during radiation medical exposure of four CT scan procedures so that local diagnostic reference levels (DRLs) could be established.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing number of CT machines in Morocco, the Diagnostic Reference Levels (DRL) have yet to be defined. Thus, several previous studies have shown a significant variation in the doses administered to patients for the same radiological examination procedure [ 20 - 26 ]. The aim of this pilot study at Hassan II Hospital of Agadir was to estimate the doses during radiation medical exposure of four CT scan procedures so that local diagnostic reference levels (DRLs) could be established.…”
Section: Introductionmentioning
confidence: 99%
“…In Morocco, the scarcity of studies on exposure to ionizing radiation during medical examinations of the population [10] [11] and on the establishment of diagnostic reference levels [12] [13] [14] [15] [16] has led us to explore the exposure of the kidneys during CT examination of the abdomen.…”
Section: Introductionmentioning
confidence: 99%
“…Medical X-ray is most common forms of radiation in medicine, and one of the largest manmade sources of radiation exposure to patients, radiology staff (workers), and the general populace, hence there exists the problem of safely delivering radiation dose when imaging biological tissues [1][2][3]. For example, conventional radiography accounts more than 80 % of X-ray-based imaging [4], and it is considered a responsible for the most of the radiation exposure associated with all medical imaging techniques [5].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, scattered radiation is considered the main source of the occupational radiation exposure [6,7]. According to ICRP Publication 103 (ICRP, 2007) the overall cancer risk coefficient has been estimated F CR = 55 mSv for the population, while F CR = 41 mSv for the adult workers [5]. Therefore, there is a need to reduce backscattered radiation dose to protect patients and radiology workers in an X-ray room from unnecessary radiation exposure [8,9].…”
Section: Introductionmentioning
confidence: 99%